Atlas of Advanced Endoaortic Surgery - Kpodonu, Jacques; Haulon, Stéphan (Springer London : Imprint: Springer, 2013)
Since the first endovascular repair of abdominal aortic aneurysm was reported in the early 1990s, there has been an explosion in the volume and complexity of endovascular and hybrid procedures for the treatment of aortic diseases. Endovascular techniques and technologies have evolved from the initial devices that allowed treatment of only the most straightforward infrarenal aneurysms with appropriately long and straight necks to the scenario that pertains today, wherein a customized endovascular solution is almost always available for even the most complex aortic aneurysm. There is growing evidence in favor of the endovascular treatment of these aneurysms, which extend above the visceral aortic segment, as well as for the treatment of thoracic aortic dissection and aneurysm. These new endoaortic surgical procedures have been proven to shorten hospitalization, reduce morbidity and mortality, speed recovery, and hasten return to normal life, while their evolution and conceptual design would obviously not be possible without the simultaneous explosion in medical imaging technologies that has taken place over a similar time period.   The Atlas of Advanced Endoaortic Surgery has been compiled to engage its readers in a comprehensive yet concise manner, with numerous illustrations of real clinical cases. It provides a useful tool for practitioners as they plan and execute treatment of patients with these various aortic pathologies, and serves as a useful reference as this segment of the field continues to evolve.